2020
DOI: 10.7150/ijbs.45115
|View full text |Cite
|
Sign up to set email alerts
|

Poly(U) binding splicing factor 60 promotes renal cell carcinoma growth by transcriptionally upregulating telomerase reverse transcriptase

Abstract: Background: Abnormal transcriptional upregulation of telomerase reverse transcriptase (TERT) plays a dominant role in telomerase activation in various cancers. TERT promoter mutations (TPMs) have been identified as a key mechanism in TERT upregulation. However, the mechanism of TERT upregulation in cancers with low frequency of TPMs are not fully elucidated so far. Methods: The expression of PUF60 and TERT was detected by real-time PCR, western blot and immunohistochemistry. TERT promoter binding proteins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…In contrast, PUF60 overexpression in renal cancer cells stimulates telomerase reverse transcriptase (TERT) transcription due to PIF60’s binding to the TERT promoter [ 69 ]. PUF60 also contributes to breast cancer progression via the PUF60-dependent downregulation of PTEN, stimulating the PI3-kinase pathway [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, PUF60 overexpression in renal cancer cells stimulates telomerase reverse transcriptase (TERT) transcription due to PIF60’s binding to the TERT promoter [ 69 ]. PUF60 also contributes to breast cancer progression via the PUF60-dependent downregulation of PTEN, stimulating the PI3-kinase pathway [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…PUF60 knockdown significantly decreased the proliferation in vitro and in vivo [ 35 ]. In renal cell carcinoma (RCC) cells, PUF60 promote cell growth and the patients with high expression of PUF60 had significantly shorter survival [ 16 ]. In our study, PUF60 is highly expressed in OC and its upregulation predicts a poor prognosis, and PUF60 promotes the proliferation and migration of OC cells both in vitro and in vivo, which is consistent with other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relative abundance of PUF60 influences the choice of alternative splice sites [ 8 ]. It has been reported that PUF60 is overexpressed in various cancers, including bladder cancer [ 9 ], colon cancer [ 10 ], hepatocellular carcinoma [ 11 ], non-small cell lung cancer [ 12 ], breast cancer [ 13 , 14 ], esophageal cancer [ 15 ] and renal cell carcinoma [ 16 ], and its overexpression is closely related to its development and progression. Studies have shown through integrated copy number and expression analysis that PUF60 may be a novel potential driver [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study Long et al. demonstrated that the upregulation of TERT promotes the growth of renal cell carcinoma (RCC) [ 15 ]. In addition, the TERT locus genotypes of rs2736100-CC/CA and rs2736098-AA have been associated with shorter survival in patients with RCC, as reported by Ma et al.…”
Section: Introductionmentioning
confidence: 99%